TRANSFORMASI KEBIJAKAN PENYIARAN DI ERA DIGITAL ANALISIS DAMPAK REGULASI OVER-THE-TOP (OTT) TERHADAP INDUSTRI TELEVISI KONVENSIONAL - Siregar, Alya Rahmayani; Sazali, Hasan (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This study explores the changing broadcasting policy in the digital context, with an emphasis on the influence of Over-The-Top (OTT) regulation on the traditional television industry. Digital transformation has drastically changed the way content is delivered and consumed, resulting in a shift from conventional television dominance to digital platforms. OTT regulation, which aims to regulate streaming service providers and digital content, has a significant impact on the existing business model, revenue, and operations of the television industry. The methodology used in this study is a qualitative approach, which includes literature studies and in-depth interviews with various stakeholders in the broadcasting sector. The findings of this study show that OTT regulation has a dualistic impact. On the one hand, this regulation provides a more structured legal basis for OTT service providers, which has the potential to encourage innovation and investment in the digital sector. However, on the other hand, the regulation also poses challenges for the conventional television industry, such as declining advertising revenue, increased competition, and the need to adapt to new technologies and business models. This shows that the television industry must face the new reality demanded by digital developments. This study concludes that an inclusive and adaptive broadcasting policy transformation is needed to achieve a balance between the development of the digital sector and the protection of the sustainability of the conventional television industry. The proposed policy recommendations include increasing collaboration between the government, OTT providers, and the television industry, as well as strengthening digital literacy among the public. These measures are expected to support the creation of a healthier and more sustainable broadcasting ecosystem amid rapid changes in the media landscape.